Fairclough’s Critical Discussion of Celebrity News in Online Media - Fitriyana, Rochmaniah; Cahyati, Sri Supiah (IKIP Siliwangi, 2025)
This discourse analysis show how Fairclough's three-part analytical approach may be applied to Mulan Jameela's celebrity internet news. This study describes the patterns and relationships in newstext online media. Its purpose is to investigate the year's most popular celebrity news. This paper made use of a qualitative study in the realm of independent investigation. It digs into Fairclough's model's methodologies and evaluates the news's intended meaning. It illustrates to readers how the creative use of simple words may shape people's ideas in a given society. The analysis is not as clean as it could be because the framework is complex and built on three distinct types of stages that are embedded one inside the other.